Design of eco-friendly PVA/TiO2-based nanocomposites and their antifungal activity study. Issue 1 (17th September 2019) - Chougale, Ravindra; Kasai, Deepak; Nayak, Shilpa; Masti, Saraswati; Nasalapure, Anand; Raghu, Anjanapura V
Abstract : In the current study, poly(vinyl alcohol) (PVA)/titanium dioxide (TiO2 )-based nanocomposite films were prepared using the solution-blending and solvent-evaporation techniques. The tensile properties and phase morphology of the prepared PVA/titanium dioxide nanocomposite films were investigated using universal testing machine (UTM) tests and scanning electron microscopy, respectively. Further, the water contact angles and antifungal activities of the composite films and their interactions were evaluated by using Fourier transform infrared spectroscopy (FTIR). The results of UTM tests revealed that the mechanical properties increased up to a proportion of 6% titanium dioxide nanoparticles. The addition of titanium dioxide nanoparticles to the PVA matrix resulted in smooth and homogeneous phase morphology except for the PVA matrix with 4% brahmi plant extract titanium dioxide nanoparticles. The water contact angle and antimicrobial activity confirmed that the hydrophilic nature slightly increased, and antifungal activity showed a significant rise in the composite films. Intermolecular interactions through hydrogen bonding between the composite films were confirmed by the FTIR study. The results of a packaging study clearly suggest that the composite films have good storage properties and they can be used as environment-friendly materials with slight modifications. The prepared films can find potential applications in food packaging for storage of foodstuffs.